Prophylactic infusion of norepinephrine does not affect the rostral spread of spinal anesthesia in pregnancy: a prospective, randomized, double-blinded study - Dong, Yu-Fang; Qian, Jing; Wang, Jing; Wang, Li-Zhong; Qian, Xing-Hua; Xiao, Fei (Frontiers in Pharmacology, 2024)
The infusion of phenylephrine to prevent spinal-induced hypotension (SIH) in cesarean delivery may decrease the rostral spread of a spinal local anesthetic.We hypothesized that infusion of norepinephrine may decrease the rostral spread of spinal anesthesia, similar to that caused by phenylephrine. The aim of this study was to compare the block height of spinal anesthesia in the presence or absence of norepinephrine infusion administered to prevent SIH during cesarean delivery.Methods: Eighty patients were enrolled and allocated into groups receiving a norepinephrine infusion (group N) or saline infusion (group C). After intrathecal injection of hyperbaric bupivacaine 10 mg, the block height for cold and pinprick sensation was checked 10 and 20 min after the injection. The demographic characteristics, spinal anesthesia, side effects, and neonatal outcomes were also recorded.The block height for cold and pinprick sensation was similar between the two groups, although the incidence of hypotension was significantly lower (P< 0.00) in group N than in group C. Systolic blood pressure was also more stable in group N than in group C, with the incidence of interventions being significantly lower in group N. There was no significant difference in patient satisfaction between the two groups.Evidence from this study suggested that prophylactic norepinephrine infusion does not reduce the rostral spread of spinal anesthesia in pregnancy. We suggest that it is not necessary to increase the dose of an intrathecal local anesthetic for cesarean delivery when prophylactic norepinephrine is administered.